Transesterification of cyclic carbonates with methanol at ambient conditions over tungstate-based solid catalysts - Sankar, M.; Nair, C. Madhavan; Murty, K. V. G. K.; Manikandan, Palanichamy (Applied Catalysis A-General, 2006)
Dimethyl carbonate synthesis with 80 mol% yield is achieved through transesterification of ethylene carbonate with methanol at ambient conditions (RT and atmospheric pressure) using alkali and alkaline-earth tungstates as solid catalysts. The catalysts are efficient even at the sub-ambient temperatures. Reactions under CO2 pressure indicate that CO2 atmosphere retards the transesterification reaction completely below 100 degrees C. Experimental conditions of 150 degrees C and 3.4 MPa CO2 pressure are required to obtain maximum DMC yield of 71 mol%. Synthesis of DMC by one-pot synthesis using epoxide, CO2 and methanol is not as effective as that by two-step method with the present catalyst system. Raman and IR spectra of methanol-interacting tungstates indicate the formation of a methoxide ion species adsorbed at the catalyst surface as one possible reaction intermediates. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: Dimethyl carbonate; ethylene carbonate; heterogeneous catalyst; Raman spectroscopy; sodium tungstate; transesterification

Electronic structure and catalytic study of solid solution of GaN in ZnO - Mapa, Maitri; Thushara, K. S.; Saha, Biswajit; Chakraborty, Purushottam; Janet, C. M.; Viswanath, R. P.; Nair, C. Madhavan; Murty, K. V. G. K.; Gopinath, Chinnakonda S. (Chemistry of Materials, 2009)
Solid solutions of GaN in ZnO (Zn1-zGaz)(O1-xNx) (x and z <= 0.15) have been prepared by simple solution combustion method, Except for minor changes in the lattice contraction, no significant change in the Wurtzite structure was observed. Raman and secondary ion mass spectrometry results show the direct Zn-N and Ga-N bonds in (Zn1-zGaz)(O1-xNx). Visible light absorption and XPS results demonstrate that N 2p states of nitride occupy the states above the O 2p valence band, and hence a change in optical band gap reduction occurs to similar to 2.5 eV from 3.37 eV for ZnO. Significant nitrogen fixation catalytic activity through NH3 formation has been observed at ambient pressure oil virgin (Zn1-zGaz)(O1-xNx) material, indicating its potential as a catalyst.

Fabrication of homogeneous nanoparticle/nanoneedle BaTiO3 and Ba0.8Sr0.2TiO3 smooth thin films by simple dip coating - Saini, Mamta; Vivekanand, K.; Poddar, Pankaj; Murty, K. V. G. K.; Thushara, K. S.; Gopinath, Chinnakonda S. (International Journal of Nanotechnology, 2010)
Ferroelectric BaTiO3 (BTO) and Ba0.8Sr0.2TiO3 (BSTO) thin film materials have been successfully prepared by sol-gel processing and simple dip coating on glass and silicon supports. Above thin films were characterised by x-ray diffraction (XRD), Raman spectroscopy, photoelectron spectroscopy, thermal analysis, atomic force microscopy (AFM) and spectroscopic ellipsometry. Phase identification of BaTiO3 and Ba0.8Sr0.2TiO3 was performed by XRD. XRD and Raman spectroscopy investigations demonstrate that thc Ba0.8Sr0.2TiO3 film exhibits tetragonal structure. AFM analysis demonstrates the elongated nanospherical particles on glass substrate and nanowires on silicon substrate, which represent a strong influence of the crystallinity of underlying substrate on the grain morphology in this technique. The thin films on both the substrates are uniformly coated without any pinhole to significant area (similar to 2.5 cm(2)), and this method might be extended to large area uniform coating. Spectroscopic ellipsometric measurements reveal the exact thickness, refractive index and extinction coefficient of the thin films.
Keywords: barium strontium titanate; barium titanate; dip coating; fabrication; ferroelectric material; large area coating; nanotechnology; thin film